2019
DOI: 10.1039/c9nr05105h
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and recovery of nano-patterned surfaces beyond the classical picture

Abstract: Here we investigate the wetting and dewetting of textured hydrophobic surfaces including inertia effects, which have been neglected in previous studies but are necessary to match experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 83 publications
(133 reference statements)
0
15
0
Order By: Relevance
“…The theoretical determination of the timescale of these processes requires the use of other advanced simulation techniques. 13,46,47 3.1 Effect of solid-liquid-gas interactions on the stability of nanobubbles…”
Section: Nanoscale Papermentioning
confidence: 99%
“…The theoretical determination of the timescale of these processes requires the use of other advanced simulation techniques. 13,46,47 3.1 Effect of solid-liquid-gas interactions on the stability of nanobubbles…”
Section: Nanoscale Papermentioning
confidence: 99%
“…Indeed, our analysis of the the intrusion in the 2D cavity by cCNT [21] revealed that several intrusion paths are possible including the nucleation and growth of a liquid droplet in the middle of the cavity or at its walls that will eventually bring to the complete filling of the texture. Nevertheless, studies based on a continuum model of the three phase system [21,46] and the corresponding atomistic representation [26,29,30] confirm that the one shown in Fig 4a is the most likely intrusion path among all possible paths.…”
Section: Descriptors Of Intrusion and Extrusionmentioning
confidence: 89%
“…This difference might be due to intrinsic differences between the experimental setup and theoretical hypotheses, first of all that insoluble gases (air) are not considered in cCNT. Moreover, forward flux sampling simulations [26,27] showed that the symmetric meniscus mechanism is more likely due to inertial effects: at the typical experimental pressures, when the intrusion barrier is small, and in absence of insoluble gasses, the liquid enters into cavities at a high speed and the meniscus does not have time to relax to the constrained equilibrium configuration. Of course, cCNT, which assumes local equilibrium, cannot model well enough highly out of equilibrium conditions.…”
Section: (A) (B) (C)mentioning
confidence: 99%
“…In this latter direction, Debenedetti and coworkers investigated the effect of wall elasticity on drying between hydrophobic plates: it was found that elasticity always favoured water evaporation [114]. Nonequilibrium effects were studied in Ref [115]., where it was found that, while in the quasi-equilibrium picture wetting and drying happen along the same path, but in different directions, the dynamics of the transition may lead to qualitatively different mechanisms, which strongly depend on pressure. It has also been reported that dissolved gases, in particular lowsolubility ones, may favour drying of nanopores [14,32]; this kind of gasassisted drying calls for further investigations, as it may play an important role in general anaesthetics [32], in controlling drying of nanoporous materials and superhydrophobic surfaces, and in the stability of surface nanobubbles [97].…”
Section: Discussionmentioning
confidence: 99%